(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Nutraceuticals, comprising supplements, herbal medicines, vitamins, and minerals, claim therapeutic benefits in addressing disease causes. Coined in 1989, the term denotes compounds promoting health. Projections suggest India's nutraceutical business will reach USD 18 billion by 2025, necessitating robust oversight. Food Safety and Standards Authority of India, established under Food Safety and Standards Act of 2006, governs approvals. This study aimed to collate data on approved, refused, and withdrawn nutraceutical products and ingredients in India from 2020 to 2023. During this period, 58 out of 110 applications, constituting 52.7%, gained approval. Notably, 20-40% of applications related to nutraceuticals faced refusal or withdrawal within the preceding four years. Factors contributing to rejections and withdrawals include the sorting of S-adenosyl-L-methionine (SAMe) as a pharmaceutical compound, non-compliance with recommended dietary intake, potential drug-like properties, misleading labeling, and insufficient evidence of product efficacy. Withdrawals often result from issues like adulteration, substandard ingredients, and noncompliance with Good Manufacturing Practices (GMP) regulations. To surmount these challenges, FSSAI must establish rigorous regulations and guidelines for nutraceutical promotion, including public notifications for any modifications, with a concurrent expectation for industries to adhere to these guidelines in promoting public health. The collaboration of applicants/nutraceutical industry, and FSSAI would foster stable expansion, as evident in the CAGR for nutraceutical products and ingredients in India.